Migrating mistakes of the publication history of the magazine „Moteris" - Genovaitė Burneikienė (Knygotyra)
Analyzing the history of Lithuanian periodicals presents many difficulties due to the lack of sources, archives, and memoirs concerning Lithuanian newspapers.